A Dual Marker for Monitoring MDR-TB Treatment: Host-Derived miRNAs and M. tuberculosis-Derived RNA Sequences in Serum - Carranza, Claudia; Herrera, María Teresa; Guzmán-Beltrán, Silvia; Salgado-Cantú, Manuel Guadalupe; Salido-Guadarrama, Ivan; Santiago, Elizabeth; Chávez-Galán, Leslie; Gutiérrez-González, Luis Horacio; González, Yolanda (Frontiers in Immunology, 2021)
Background. In the absence of a late marker of treatment failure or relapse in MDR-TB patients, biomarkers based on host-miRNAs coupled with M. tuberculosis-RNAs evaluated in extracellular vesicles (EVs) are an alternative follow-up for MDR-TB disease. Characterization of EVs cargo to identify differentially expressed miRNAs before and after treatment, and to identify M. tuberculosis-derived RNA in serum EVs from resistant TB patients. Methods. EVs were isolated from serum of 26 drug-resistant TB (DR-TB) patients and 16 healthy subjects. Differential expression of miRNAs in pooled exosomes from both untreated and treated patients was assessed and individually validated at different time points during treatment. In addition, M. tuberculosis RNA was amplified in the same samples by qPCR. Results. A multivariate analysis using miR-let-7e-5p, -197-3p and -223-3p were found to be a more sensitive discriminator between healthy individuals and those with TB for both DR-TB (AUC= 0.96, 95%, CI=0.907-1) and MDR-TB groups (AUC= 0.95, 95%, CI= 0.89-1). Upregulation of miR-let-7e-5p were observed at the time of M. tuberculosis negative culture T(3-5) for MDR-TB group or for long-term T(9-15) for MDR-TB group without diabetes (T2DM). A second pathogen-based marker based on 30kDa and 5KST sequences was detected in 33% of the MDR-TB patients after the intensive phase of treatment. The miR-let7e-5p is a candidate biomarker for long-term monitoring of treatment for the group of MDR-TB without T2DM. A dual marker of host-derived miR-let7e-5p and M. tuberculosis-derived RNA for monitoring-TB treatment based in serum EVs. Conclusion. A dual marker consisting of host-derived miR-let7e-5p and M. tuberculosis-derived RNA, could be an indicator of treatment failure or relapse time after treatment was completed.